Ru(II)-Fenamic-Based Complexes as Promising Human Ovarian Antitumor Agents: DNA Interaction, Cellular Uptake, and Three-Dimensional Spheroid Models - Teixeira, Tamara; Palmeira-Mello, Marcos V.; Machado, Pedro Henrique; Moraes, Carlos A. F.; Pinto, Camila; Costa, Rayane C. [UNESP]; Badaró, Wladimir [UNESP]; Gomes Neto, José A. [UNESP]; Ellena, Javier; Vieira Rocha, Fillipe; Batista, Alzir A.; Correa, Rodrigo S. (American Chemical Society (ACS), 2025)
Cancer resistance to chemotherapeutic agents such as cisplatin presents a significant challenge, leading to treatment failure and poor outcomes. Novel metal-based compounds offer a promising strategy to overcome drug resistance and to enhance efficacy. Four Ru(II) complexes with fenamic acid derivatives were synthesized and characterized: [Ru(L)(bipy)(dppp)]PF6, where L represents fenamic acid (HFen, complex 1), mefenamic acid (HMFen, complex 2), tolfenamic acid (HTFen, complex 3), and flufenamic acid (HFFen, complex 4). Their composition was supported by molar conductivity, elemental analysis, Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, mass spectrometry, and 31P{1H}, 1H, and 13C nuclear magnetic resonance, with the crystal structure of complex 1 confirmed via X-ray diffraction. Complexes 1-4 exhibited notable cytotoxicity against tested cell lines, particularly A2780 and A2780cisR (cisplatin-resistant ovarian tumors), compared to MDA-MB-231 (breast) and A549 (lung) lines. Mechanistic studies revealed weak DNA interactions through minor grooves or electrostatic binding. Cellular uptake assays showed effective internalization of complexes 1 (3.6%) and 2 (4.5%), correlating with potent IC50 values. These complexes also altered cell morphology, reduced cell density, and inhibited colony formation in the A2780 cells. Staining assays indicated induced cell death and organelle damage, highlighting their potential as promising antitumor agents.